2020
DOI: 10.1038/s41598-020-73751-4
|View full text |Cite
|
Sign up to set email alerts
|

Importance of cholesterol-rich microdomains in the regulation of Nox isoforms and redox signaling in human vascular smooth muscle cells

Abstract: Vascular smooth muscle cell (VSMC) function is regulated by Nox-derived reactive oxygen species (ROS) and redox-dependent signaling in discrete cellular compartments. Whether cholesterol-rich microdomains (lipid rafts/caveolae) are involved in these processes is unclear. Here we examined the sub-cellular compartmentalization of Nox isoforms in lipid rafts/caveolae and assessed the role of these microdomains in VSMC ROS production and pro-contractile and growth signaling. Intact small arteries and primary VSMCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 76 publications
(115 reference statements)
0
11
0
Order By: Relevance
“…Regarding NOX5 localization, mainly in the acrosome region and the apical edge, we have demonstrated that it changes during ram sperm capacitation. To explain this redistribution we could hypothesize that NOX5 could be embedded in lipid rafts, as it has been demonstrated in somatic cells (Anagnostopoulou et al, 2020). During the capacitation process, the cholesterol efflux from the sperm membrane allows the reorganization of the lipid rafts (van Gestel et al, 2005), giving new protein distributions, and modulating their activity (Kawano et al, 2011).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Regarding NOX5 localization, mainly in the acrosome region and the apical edge, we have demonstrated that it changes during ram sperm capacitation. To explain this redistribution we could hypothesize that NOX5 could be embedded in lipid rafts, as it has been demonstrated in somatic cells (Anagnostopoulou et al, 2020). During the capacitation process, the cholesterol efflux from the sperm membrane allows the reorganization of the lipid rafts (van Gestel et al, 2005), giving new protein distributions, and modulating their activity (Kawano et al, 2011).…”
Section: Discussionmentioning
confidence: 84%
“…During the capacitation process, the cholesterol efflux from the sperm membrane allows the reorganization of the lipid rafts (van Gestel et al, 2005), giving new protein distributions, and modulating their activity (Kawano et al, 2011). This lipid raft redistribution was demonstrated to be the mechanism by which NOX5 could modulate its activity, in certain somatic cells (Anagnostopoulou et al, 2020). The cytoskeleton plays a fundamental part in the rearrangement of the membrane during sperm capacitation (Brener et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the fact that NOXs have been reported to be found within caveolae in endothelium [ 23 , 24 ], as well as in adipose tissue [ 19 ], and that they can interact with CAV1, raises the possibility of a cross-regulation, something that deserves further investigation. In regard to this, it is interesting the finding that ROS may enhance CAV1 transcription in NIH-3T3-L1 fibroblasts [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…A direct interaction between caveolae and NOX enzymes has also been shown. A recent study has revealed that NOX5 is present in caveolae from vascular smooth muscle cells [ 23 ]. In this regard, it has been described that CAV1 can bind to NOX5 promoting a decrease of its activity [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has documented that NOX1 and NOX5, but not NOX4, localize in cholesterol-rich fractions in intact human vascular smooth muscle cells from patients undergoing elective craniofacial surgeries [27]. These results suggest an essential role of lipid rafts/caveolae in the signaling platforms for specific NOX isoforms in intact human vascular smooth muscle cells.…”
Section: Noxs In the Human Vascular Smooth Muscle Cellsmentioning
confidence: 93%